Digital transformation of business-to-business sales: what needs to be unlearned?. Issue 2 (3rd April 2021) - Mattila, Malla; Yrjölä, Mika; Hautamäki, Pia
Abstract: This study aims to offer novel means for rethinking contemporary business-to-business (B2B) sales operations and the assumptions that underlie them in the digital era. This rethinking relates especially to sales managers' efforts to facilitate cognitive unlearning in B2B sales management during the ongoing digital transformation taking place in enterprises. Unlearning—the process of purposely reflecting on and discarding old ways of knowing and doing—is crucial to prevent outdated organizational knowledge and routines from becoming a barrier to change. Before adopting new sales practices, sales organizations must first discard old ways of knowing and doing. Drawing insights from unlearning and B2B sales management literature and conducting empirical qualitative research on 31 executives and senior managers operating in various industries, the study outlines a four-phase process for unlearning as well as several key themes within each phase. The findings emphasize how top management facilitates cognitive unlearning regarding digital business transformation in the B2B sales context. The study contributes to sales management literature by introducing cognitive unlearning as a new theoretical angle on the issue of digital transformation. It also offers insights for sales managers on how to elevate and leverage the unlearning of salespeople.